Association between Cortisol and Infection Risk of Children with Acute Lymphoblastic Receiving Induction and Consolidation Chemotherapy in Dr. Soetomo General Hospital Surabaya - Tutwuri Handayani; Dewa Gede Ugrasena; Mia Ratwita Andarsini (Institute of Medico-legal Publications Pvt Ltd, 2022)
Background: Mortality due to Infection associated therapy in acute lymphoblastic leukemia (ALL) children remains high, although therapeutic success and survival rate are substantially improving.Methods: This study used a pre and post-test group design for children aged less than 18 years with ALL newly diagnosed and receiving chemotherapy in pediatric patient of Dr. Soetomo hospital Surabaya.Results: The study involved 25 subjects, 10 subjects were male, average age ranged from 3 to 9 years. The high risk-ALL subjects were 15 (60%), hyperleukocytosis 4 (16%) subjects and 7 (28%) subjects with leukopenia. Statistical analysis showed a significant difference in decreasing cortisol levels in week-4 compared to week-0 (p <0.001) and an increased in cortisol levels between week-12 compared to week-10. The incidence of infection during induction phase is higher than the consolidation phase (40vs15). The relationship between the mean cortisol levels and the incidence of infection in general showed a significant difference in the induction phase of week-0 (p=0.029), week-4 (p=0.041), and week-6 (p=0.005).Conclusion: In the induction phase, there is an association between mean cortisol levels and the risk of infection, but there is no such association in the consolidation phase.